کاریگەریی پیداگۆجی داهێنەرانە لەسەر دەستکەوتی خوێندکاران (وانەی مێژوو بە نمونە) - قادر, پ.د. ابتسام اسماعیل; محمد, شەنگ محمد دلێر (Sulaimani Journal for Humanities, 2023)
The title of this research is (The importance of media education in the era of digital media among students of Sulaimani University). The researcher relied on descriptive method using survey method in order to achieve the objectives and present the results. The research community is Sulaimani University and its sample is university students. The most important objectives of thes research are to introduce the concept of media education and digital media, to show the level of media attention to media education and to reveal the relationship between media education and digital media. The most important conclusions reached by the researcher are: 1- Media education introduces students to the negative consequences of the media. 2- Media education leads to a deeper understanding of media messages 3- The weakness of the media is the reason for the lack of media education 4- Media education has been able to benefit from digital media 5- Digital media has become a means of exchanging information and scientific articles among university students